Manual of neuro-ophthalmology - Agarwal, Amar (Jaypee Brothers Medical Publishers (P) Ltd., 2015)
The book includes chapters on ocular myopathies and miscellaneous conditions, including pituitary tumours, carniopharyngioma, headache, functional visual loss and carotid cavernous fistula. The final chapter covers imaging methods in neuro-ophthalmology, with discussion on computed tomography, congenital pathology of optic pathways, intracranial pathology of the visual pathway, and sellar tumours. This new edition includes a new chapter on Optic Nerve Sheath Fenestration, an operation on the connective tissue lining of the optic nerve, and an examination of a neuro-ophthalmology case. With 150 full colour images and illustrations, Manual of Neuro-ophthalmology is a clear and comprehensively updated guide to a complicated field of medicine, ideal for both students and practising ophthalmologists.